Pemberdayaan Masyarakat Lokal Melalui Ecoprint: Studi Kasus di Surami Collection - Kezia Verty; Rita Yunus; Eko Jokolelono; Yunus Sading; Meity Ferdiana Paskual (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research is motivated by the creative economy of the Kalukubula area which is believed to be able to absorb labor. One of them is the ecoprint creative economy in Sigi Regency, Kalukubula Village. The ecoprint creative economy in Kalukubula village can reduce the unemployment rate for housewives and also improve the community's economy for the better, including the economic situation of employees and business owners. However, a creative economy such as ecoprint cannot be separated from the problem of minimal market share. This research uses descriptive research with a qualitative approach. Data was collected through interviews. The sample size used in this research was one respondent. Respondents are involved in the ecoprint business in the Sigi area. The aim of this research is to describe the economic empowerment of the community in Sigi Regency, Kalukubula Village and determine the empowerment of local communities through ecoprint.